Traumatic Hip Dislocation Associated with Proximal Femoral Physeal Fractures in Children: A Systematic Review - Oana Haram; Elena Odagiu; Catalin Florea; Iulia Tevanov; Madalina Carp; Alexandru Ulici (Children, 2022)
Traumatic hip dislocation might lead to serious complications and a poor outcome. Fortunately, it is a rare condition in pediatric patients. The purpose of this study is to establish and describe the complications caused by hip dislocations associated with transphyseal femoral neck fractures. Therefore, we conducted a literature review that resulted in 11 articles, including 32 patients, older than 10 years of age, suffering from traumatic hip dislocation associated with a transphyseal femoral neck fracture. We presented a case series of three patients with hip fracture-dislocation treated in our clinic that were also evaluated and included in the study. For the 35 patients included in the study group, the percentage of avascular osteonecrosis after hip fracture-dislocation was 88.57%. Traumatic hip dislocation associated with transphyseal femoral neck fracture is a rare condition and has a poor prognosis because of the high incidence of femoral head avascular necrosis (AVN). Reduction should be attempted within six hours the from injury, but this may not minimize the risk of AVN if transphyseal separation occurs. The approach may influence the development of AVN; lateral approach of the hip with great trochanter osteotomy seems to have the lowest number of cases of AVN.